PENGARUH PENGGUNAAN HANDOUT YANG DILENGKAPI PETA KONSEP BERGAMBAR TERHADAP KOMPETENSI BELAJAR BIOLOGI SISWA KELAS VIII SMPN 31 PADANG TAHUN PELAJARAN 2013/2014 - Puspita, Suri - (STKIP PGRI Sumbar, 2014)
Teaching and learning process in SMP 31 Padang is still teacher centered. Instructionalmedia use less variable, and the results of their study are still under minimum completenesscriteria. This study aimed to determine the effect to the handout that comes with pictorial conceptmap of learning competencies Biology eighth grade students of SMP Negeri 31 Padang. This studyis an experiment with purposive cluster sampling. The cognitive test instruments in the form ofmultiple choice questions. Non test instrument on the affective and psychomotor form ofmotivation questionnaire, observation sheet activities, and student assignment assessment sheet.Based on the analysis of data on the average cognitive learning outcomes experimental class 87.33and control class 75.34. In the Uji-t is obtained thitung 4.80 and 1.67 ttabel. In the affective domain ofstudent motivation in the experimental class 89% and control class 83.46%. Activity of students inthe first meeting of the experimental class 64.37%, and the second meeting 63.12%. In the firstclass meeting control 29.50%, and the second meeting 23.93%. In the psychomotor, the averagestudent assignments in the experimental class 63,60 and control class 34,86. Based on the dataanalysis it can be concluded that the use of a handout that comes with pictorial concept mapsaffect the learning competencies Biology at the second semester of eighth grade students at SMPNegeri 31 Padang.